Pengaruh Ukuran Perusahaan, Ukuran Dewan Komisaris, Dan Pengungkapan Modal Manusia Terhadap Kinerja Perusahaan di Indonesia - Reka Davinda; Mukhzarudfa Mukhzarudfa; Gandy Wahyu Maulana Zulma (Ekonomis: Journal of Economics and Business, 2021)
This study aims to empirically prove the effect of firm size, board of commissioners and human capital disclosure on firm’s performance of consumer goods industry companies listed on the Indonesia Stock Exchange from 2015 - 2019. The independent variables in this study are firm size, board of commissioners, and human capital disclosure with the dependent variable is firm’s performance. The sample used in this study is data from consumer goods industry companies listed on the Indonesia Stock Exchange for the period 2015-2019 with a purposive sampling method of 25 companies. The analytical method used in this research is multiple linear regression analysis. The founds from this study show that board of commissioners and human capital disclosure are affecting firm’s performance, while firm’s size doesn’t affect firm’s performance.